Distinct Roles of Heterogeneous Nuclear Ribonuclear Protein K and microRNA-16 in Cyclooxygenase-2 RNA Stability Induced by S100b, a Ligand of the Receptor for Advanced Glycation End Products - Shanmugam, Narkunaraja (American Society for Biochemistry and Molecular Biology, 2008)
Advanced glycation end products play major roles in diabetic complications. They act via their receptor RAGE to induce inflammatory genes such as cyclooxygenase-2 (COX-2). We examined the molecular mechanisms by which the RAGE ligand, S100b, induces COX-2 in monocytes. S100b significantly increased COX-2 mRNA accumulation in THP-1 monocytes at 2 h via mRNA stability. This was further confirmed by showing that S100b increased stability of luciferase-COX-2 3′-UTR mRNA. Chromatin immunoprecipitation and RNA immunoprecipitation revealed that S100b decreased occupancy of the DNA/RNA-binding protein, heterogeneous nuclear ribonuclear protein K (hnRNPK), at the COX-2 promoter but simultaneously increased its binding to the COX-2 3′-UTR. S100b treatment promoted the translocation of nuclear hnRNPK to cytoplasm, whereas a cytoplasmic translocation-deficient hnRNPK mutant inhibited S100b-induced COX-2 mRNA stability. Small interfering RNA-mediated specific knockdown of hnRNPK blocked S100b-induced COX-2 mRNA stability, whereas on the other hand, overexpression of hnRNPK increased S100b-induced COX-2 mRNA stability. S100b promoted the release of entrapped COX-2 mRNA from cytoplasmic processing bodies, sites of mRNA degradation. Furthermore, S100b significantly down-regulated the expression of a key microRNA, miR-16, which can destabilize COX-2 mRNA by binding to its 3′-UTR. MiR-16 inhibitor oligonucleotides increased, whereas, conversely, miR-16 mimic oligonucleotides decreased COX-2 mRNA stability in monocytes, further supporting the inhibitory effects of miR-16. Interestingly, hnRNPK knockdown increased miR-16 binding to COX-2 3′-UTR, indicating a cross-talk between them. These new results demonstrate that diabetic stimuli can efficiently stabilize inflammatory genes via opposing actions of key RNA-binding proteins and miRs.